Corporate Governance Mechanisms and Capital Structure - Saleh F A Khatib , Dewi Feriha Abdullah , Ernie Hendrawaty , Ibrahim Suleiman Yahaya (International Journal of Advanced Science and Technology, 2020)
The purpose of this article is to review studies on corporate governance and capital structure association and to proffer a precise understanding of its findings. There remains a good deal of uncertainty about this association. We shall argue that there is an incompatibility between the theories and reality. For example, agency and resource dependency theories predict this association to be positive, the general documented evidence is an inverse association between the cited variables. Yet, these theories are the most common in the literature. However, more multiple-theory oriented research is needed. In the view of the need for more review articles to guide future research, as it is less common in the literature, this article contributes to the literature not only in terms of evaluating the existing studies, assessing the inconsistent findings and identifying gaps but also sheds the light on the importance of some mechanisms of corporate governance that have been overlooked like board cognitive and demographic diversity (such as board tenure, gender, experience, etc.).